Conversion of paddy straw to bioethanol through consolidated bioprocessing using lignocellulolytic fungi - Mohamed Ghazali, Mona Fatin Syazwanee (2019)
Normally, paddy straw was disposed of via open burning even though it contains valuable lignocellulosic materials which can be readily converted into fermentable sugar for bioethanol production. The second-generation of bioethanol production utilizes useful lignocellulosic substrates especially cellulose for bioconversion process. However, this material is enclosed within hemicellulose and lignin matrix in the cell wall, making the accessibility of cellulose become the major problem in bioethanol production from such sources in consolidate bioprocessing (CBP). The CBP is preferable as it produces faster saccharification result, low risk of contamination and cost-effective. Nevertheless, finding an optimize condition for efficient bioethanol production in CBP is still ambiguous as a different strain of lignocellulolytic fungi has their own environment preferences. Therefore, the main aim of this study is to explore a new approach in converting paddy straw into bioethanol using only filamentous fungi throughout the entire CBP process, thus eliminating the use of yeast as a fermenter organism. In this study, the research objectives involves the pretreatment method of paddy straw, selecting the best lignocellulolytic agent for hydrolyzation, optimizing all factors influencing the bioethanol production via one-factor-at-a-time (OFAT) as well as Response Surface Methodology analysis (RSM) and evaluating the final CBP set-up. Paddy straw sieved into three different sizes; 2 mm, 5 mm and 8 mm were prepared and underwent several physical pretreatment (autoclave, boil) and chemical pretreatment (HNO3 and NaOH). Size five millimeter paddy straw showed the highest cellulose content (35.61%) and the percentage of cellulose content went escalated to 72.47% when pretreated with 2% (w/v) sodium hydroxide (NaOH). Pretreatment of 2% (w/v) NaOH also shown the most efficient delignification and desilication process (1.02% lignin; 5.44% ash content) compared to others. All strains of fast-growing fungi were quantitatively assayed and the results indicate that the highest cellulases enzyme producer were Trichoderma asperellum B1581 (3.93 U/mL endoglucanase; 2.37 U/mL exoglucanase; 3.00 U/mL β-glucosidase; 54.87 U/mL xylanase), followed by Aspergillus niger B2484 (5.60 U/mL endoglucanase; 1.08 U/mL exoglucanase; 1.57 U/mL β-glucosidase; 56.85 U/mL xylanase). A further test on compatibility test revealed mutual intermingling between both T. asperellum B1581 and A. niger B2484. Six single factors that are crucial for bioethanol production were tested in one-factor-at-a-time (OFAT) analysis for both selected strains of lignocellulolytic fungi. With all factors combined, T. asperellum B1581 prefers 2 days of both saccharification and fermentation process at 30°C with an amount of 3% substrate level and 10% of media level. While A. niger B2482 prefers 3 days of saccharification, 1 day of fermentation; at 30°C with an amount of 2% substrate level and 20% of media level. The results produced by OFAT were used as the centre point in the Central Composite Design (CCD) through Response Surface Methodology (RSM) software. However, comparison between the actual and the predicted value of ethanol produced in RSM’s recommended CBP set-up for both T. asperellum B1581 and A. niger B2484 showed no significant difference, thus proving the model’s stability to navigate experiment. In order to test effectiveness T. asperellum B1581 and A. niger B2484 as a fungi consortium, several combination of consortia concentrations (spore/mL) were tested and the amount of ethanol was quantified. However, a single strain of T. asperellum B1581 (6:0) was able to match the amount of ethanol produced by consortia of T. asperellum B1581 and A. niger B2484 (5:1, 4:2, 3:3, 2:4 and1:5) by producing the highest total amount of ethanol (1.11 g/L). The final amount of ethanol detected by GC-FID was 1.25 g/L; which was not significantly different from the ethanol assayed spectrometrically (1.11 g/L). As a conclusion, a pretreatment of size 5 mm using 2% (w/v) NaOH had enhanced the breaking of cellulose-lignin complex, delignification, and desilication. Thus making the paddy straw becomes feasible for biofuel production. Both T. asperellum B1581 and A. niger B2484 were found to produce the highest cellulase enzyme and displayed mutual intermingling relationship suggesting the possibility of fungal consortium formation between these two species. Even though the recommended model for CBP set-up by RSM showed no significant differences between an actual and predicted value of ethanol produced, both species unable to improve the value of ethanol produced as consortia compare to single T. asperellum B1581 culture set-up. Thus, indicating that the potential of T. asperellum B1581 as single culture for bioethanol production in consolidated bioprocessing (CBP).